2021
DOI: 10.17762/turcomat.v12i5.1484
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Positivity at Workplace in Context of Spirituality: A Conceptual Framework

Abstract: Happiness when associate with spirituality in the workplace may be one of the hardest tasks for the employees who have ever witnessed. The potential threat to manage work with happiness in every profession due to competition, expectations and new challenges has engulfed the organizations by now. Employees react differently in their style that depends on how much the individual is spiritual and reflecting happiness at the workplace. This paper attempts to determine the ways to remain happy at the workplace with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Also, all nine factors had a positive significant effect on barriers to organizational vitality. These results are somehow consistent with the results of studies by Masouminezhad et al (2021), Dhamija (2021), Shojaei et al (2020), Adabi et al (2020), Jovari et al (2020), Hadian & Rahmanzade (2018), Taherian et al (2014) and Fani & Aghaziarati (2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, all nine factors had a positive significant effect on barriers to organizational vitality. These results are somehow consistent with the results of studies by Masouminezhad et al (2021), Dhamija (2021), Shojaei et al (2020), Adabi et al (2020), Jovari et al (2020), Hadian & Rahmanzade (2018), Taherian et al (2014) and Fani & Aghaziarati (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Masouminezhad, Farrokhseresht, Alavi & Taghipourian Gilani (2021) concluded in a research that the drivers of organizational vitality included job, management and leadership, well-being, contextual, physiological, personality, belief, skill, communication and organizational citizenship behaviors. Dhamija et al (2021) in a research concluded that spirituality and religion, positive thinking, learning, honesty, participation and work interest played an effective role in employee vitality. Shojaei, Bagheri, Nikbakht & Mohseni Beykzadeh (2020) investigated the factors affecting organizational vitality, and found 11 factors, namely trust, optimism, job satisfaction, job and economic security, specific and common work goals, organizational commitment, organizational learning, sense of justice, honesty, work interest and the meaningfulness of work.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from managing the task force in the workplace, workplace spirituality also benefits firms by acquiring corporate sustainability, as workplace spirituality (WPS) and organizational citizenship behaviour (OCB) both reinforce workplace behaviour in a positive orientation (Hafeez et al, 2022). Workplace spirituality and its need in the current workplace scenario are well explained using the Alexander Krolof Model, which indicates attributes like thinking positively, learning, self-opening, participation, meaningful work, and interests in work could potentially drive employees to remain happy at the workplace (Dhamija, 2021).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…Like OCB, WPS also orients workplace behavior positively (Hafeez et al, 2022). From the literature, it is evident that WPS is the need of the hour, and it is well explained in the Alexander Krolof Model, which indicates that attributes such as thinking positively, learning, self-opening, participation, meaningful work, and interests in work could potentially drive employees to remain happy in the workplace (Dhamija, 2021). Thus, inculcating WPS or creating awareness about WPS practices in employee development programmes will promote healthier employee outcomes (Riasudeen & Singh, 2020), and it will drive higher positive affectivity, resilience, self-efficacy, work engagement (Dal et al, 2020), and employee engagement and mental health (Sharma & Kumra, 2020).…”
Section: Existing Literaturementioning
confidence: 99%